Overview and prospect of information and communication technology development in virtual power plants. Issue 6 (24th December 2022) - Li, Bin; Wang, JingJu; Bai, XueFeng; Tang, TianYue; Zhao, JianLi; Liu, Chuan; Hou, ZhanSheng; Banimenia, Izzeddin; Ali, Rashid
Abstract: As a new energy‐supply service solution to address massive, distributed energy access to the power system, a virtual power plant has higher transmission reliability and real‐time communication requirements. To achieve collaborative optimisation, distributed load and energy resources must be aggregated using new information and communication technology. This study analyses underlying communication technologies for virtual power plant interaction from the perspective of standardisation, efficiency, reliability, and security, summarises the application of blockchain, cloud‐edge collaboration, machine learning, and other new information and communication technologies in virtual power plant energy trading, interaction, and scheduling, and proposes ideas for addressing shortcomings in interaction. To improve virtual power plant interaction, performance parameter mapping between communication and business technology, and multilevel virtual power plant interaction technology are proposed.